Mechanisms of Lung Injury and Bronchopulmonary Dysplasia - Jobe, Alan H. (American Journal of Perinatology, 2016)
Although bronchopulmonary dysplasia (BPD) is the most frequent adverse outcome for infants born at < 30 weeks gestational age, there remain major gaps in understanding the pathophysiology, and thus there are few effective targeted therapies to prevent and treat BPD. This review will focus on the substantial problems and knowledge gaps for the clinician and investigator when considering lung injury and BPD. The epidemiology of BPD is clear: BPD is a lung injury syndrome predominantly in extremely low-birth-weight infants with an incidence that increases as gestation/birth weight decrease, with growth restriction, in males and with fetal exposures and with injury from postdelivery respiratory care. However, we do not have a good definition of BPD that identifies the infants that die of respiratory disease before 36 weeks or that predicts long-term outcomes as well. The injury resulting in BPD likely begins as altered lung development before delivery in many infants (small for gestational age, chorioamnionitis, tobacco exposure), can be initiated by resuscitating at birth, and then amplified by postnatal exposures (oxygen, mechanical ventilation, infection). Conceptually the events leading to BPD are the continued interplay of lung development that is altered progressively by injury and repair to result in poorly defined phenotypes of BPD. The injury pathways prominently cause inflammation, and as a proof of principle, corticosteroids can decrease the incidence and severity of BPD, as demonstrated by three recent trials of the early use of steroids. There are likely “adaptation” and “tolerance” responses that modulate the injury and repair to increase or decrease the damage, interactions that are not understood. BPD is a more complex disease.
Keywords: lung injury; injury repair; postnatal steroids; injury tolerance